ENVIRONMENTALLY FRIENDLY PROCESSING OF HARNESS LEATHER - DANYLKOVYCH, Anatolii; SANGINOVA, Olga (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the results of the development of the technology of sintal-tanid tanning of unhaired hide obtained from the skins of cattle - heavy beef with acid deaeration, in the formation of harness skin without the use of chromium compounds. For this, the samples of the unhaired hide are thoroughly washed with water according to the usual method, and soaking is performed on the residual liquid after draining (20%) in a drum for 2 hours at a temperature of 19–20 C in the presence of 0.5% ammonium sulfate and 0.6% lactic acid mixture and sulfuric at a ratio of 1:1 based on 100% concentration. Reagent consumption are set based on the previous studies. Sodium hexametaphosphate in the presence of 100% water by weight of the semi-finished product (PK 1) for the same temperature is used to transform the unhaired hide into pre-tanning components. After 15 minutes of mixing in a drum 0,6% of the sulfuric acid diluted with water 1: 5 are added. For 30 minutes external layers of a branch are preliminary fixed. Then a second pre-tanning is performed due to the addition of 1.5% formalin. After 4 hours of continuous rotation of the drum, for the next 12 hours the system is set in motion for 2-3 minutes every 2 hours. During this time, the pH value of the cut of the semi-finished product is 4.6. To reduce the content of environmentally hazardous reagents, formalin is excluded from the technological process. The use of sodium hexametaphosphate and formaldehyde instead of chromium compounds before syntane-tanide tanning allows to reduce the duration of the technology by 18 hours, to reduce water consumption by 1.6–2.2 times. When using only sodium hexametaphosphate at the stage of pre-tanning and tanning of the semi-finished product of the developed technology, the toxic substances content in wastewater of leather production is significantly reduced. Harness leather produced using the developed chrome-free tanning technology meets the technical requirements of the current standard in terms of its quality. Tested chemical materials can be effectively used for the development of alternative chrome, environmentally safer, resource-saving technologies to produce leather materials for general purposes.
Keywords: heavy beef; shaving; tanning; diffusion of tannins; harness leather; physicochemical properties